PENGARUH PUPUK HAYATI KAYABIO DAN CARA PEMUPUKAN TERHADAP PERTUMBUHAN DAN HASIL JAGUNG (Zea mays L.) - Sundari Sundari; Erwin Arief Rochyat; Ervina Sary (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
This study aims to determine the effect of Kayabio biofertilizer and fertilization methods on the growth and yield of corn (Zea Mays L.). The study began in September to December 2018, located on the farm land of Marangan Hamlet, Loh Sumber Village, Loa Kulu District, Kutai Kartanegara Regency, East Borneo Province.The study was arranged in Factorial Randomized Complete Block Design (RCBD) consisting of 2 factors and repeated 3 times. The first factor was the administration of Kayabio (p) biological fertilizer which consisted of 4 levels, namely p0 (without fertilizer), p1 (18 g plot-1), p2 (36 g plot-1), p3 (54 g plot-1). And the second factor is How to Fertilize (c) which consists of 3 levels, namely c1 (way of Portugal), c2 (how to run) and c3 (spread).The results showed that Kayabio biofertilizer had no significant effect on all observed parameters. The highest yield on average yield of dry seed shelled t ha-1 is on p3 with an average yield of 3.78 t ha-1 and the lowest yield of dry seed shell weight t ha-1 is at p0 with an average yield of 4,19 t ha-1.The results showed that the fertilization method had no significant effect on all observational parameters. The highest yields of average dry seed seed weight t ha-1 are in c1 with an average yield of 4.20 t ha-1 and the lowest yield of dry seed shell weight t ha-1 is in c3 with an average yield of 3.80 t ha-1.The results of the interaction between Kayabio biofertilizer and fertilization methods had no significant effect on all observational parameters. The highest yields of average dry seeds of shelled beans t ha-1 were at p3c1 with yields of 4.61 t ha-1 and the lowest yields of yields of dry seeds of shelled beans t ha-1 were in treatment p1c3 with a yield of 3.59 t ha-1. Key words : Kayabio biofertilizer, fertilization method and corn production